2021
DOI: 10.1556/030.2021.01606
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of vaccine-related high-risk human papillomaviruses and their impact on the development of cervical dysplasia in women in Montenegro

Abstract: Cervical cancer (CC) is the third leading cause of death in women in Montenegro. Human papillomavirus (HPV) is the causative agent of CC however, HPV genotype distribution varies across regions. This study examined the distribution and impact of vaccine-related high-risk (HR)-HPVs on the development of cervical dysplasia in Montenegrin women. A total of 187 women who had a clinical indication for cervical biopsy were enrolled. Based on histopathological findings, women were classified into 2 groups, with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
0
0
Order By: Relevance
“…The only available data on HR-HPV infection prevalence in Montenegrin population relies on the study conducted among women with suspected cervical dysplasia. In this research, high HR-HPV infection prevalence (40.6%) was shown among examined women, with the genotype 16 being the most prevalent in cases with proven dysplasia (28.9%) [17].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The only available data on HR-HPV infection prevalence in Montenegrin population relies on the study conducted among women with suspected cervical dysplasia. In this research, high HR-HPV infection prevalence (40.6%) was shown among examined women, with the genotype 16 being the most prevalent in cases with proven dysplasia (28.9%) [17].…”
Section: Discussionmentioning
confidence: 52%
“…Results of the previously mentioned research in Montenegro are indicating that prophylactic nonavalent vaccine can potentially prevent approximately 90% of HR- HPV infections and 60% of cervical dysplasia cases in Montenegrin women [17].…”
Section: Males Femalesmentioning
confidence: 96%
See 1 more Smart Citation
“…In the countries of our region, a higher percentage of HPV infection was recorded in Croatia (59%) [ 19 ], and in the territory of Italy (53%) [ 23 ]. Lopicic et al (2021) found nearly the same HPV infection rate (41%) in examined Montenegrin women [ 24 ]. Ursu et al (2011), in Romanian women, proved the presence of HPV infection in 37% [ 25 ], while more recent data showed a lower prevalence (12%) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%